O “Tien” feito carne: Os Jesuítas e a formação do “cristianismo chinês” - Vitor Ribeiro, António (Coimbra University Press, 2025)
The Jesuit mission in the East, and in China in particular, has been the subject of classic missological history studies, many of them of the highest quality. The aim of this publication is not to take a missological approach, but rather to study the possibilities and compatibilities of Christianity in a Confucian cultural environment. The aim is to look at the documentation from an ethnological, anthropological and philosophical point of view. The materials used range from accounts of exorcism rituals, dreams of journeys to the afterlife, Confucian cultural practices penetrated by Christian elements, conversations between missionaries and peasants, Buddhists, Taoists, mandarins and emperors. On another level, the aim is to place the Jesuit mission in China (1600-1750) in a perspective of cultural exchange, in which events in the Chinese mission were often determined by developments taking place in Europe, namely the rise of Jansenism from the second half of the 17th century. This approach, using indicative, quasi-police methodologies, also aims to shed new light on the famous question of “Chinese rites”.